THE SOCIO-POLITICAL CONCEPTUAL FOUNDATIONS OF INFORMATION AND THE INFORMATION SPACE (Scientific journal of the Fergana State University, 2026)
Information and knowledge have played an important role in all periods of the development of society. Understanding the relationship between information and knowledge is of particular importance in cases related to the essential understanding of the importance and role of information in the life of society. The fact that information and knowledge are distinguished by their aspects manifested in all areas of the human factor is one of the important scientific and philosophical issues. The article describes the use of databases to establish correlations and trends instead of searching for individual facts, and the extraction of scientific information through information operations.